Evaluation of the Umbrella Species Concept at Fine Spatial Scales. Issue 2 (27th November 2019) - Barlow, Natasha L.; Kirol, Christopher P.; Doherty, Kevin E.; Fedy, Bradley C.
Abstract : At the nest‐shrub and nest‐patch scale, greater sage‐grouse is an effective umbrella for Brewer's sparrow in our region. Local habitat management for greater sage‐grouse as a proxy for conservation of other species may be justified if the microhabitat preferences of the species under the umbrella are well understood to avoid unintentional negative effects. ABSTRACT: Declines in the spatial extent of the sagebrush ecosystem have prompted the consideration of conservation efforts that view the greater sage‐grouse ( Centrocercus urophasianus ; sage‐grouse) as an umbrella species at landscape scales. Conservation strategies that focus on an umbrella species, however, may have unintended negative consequences for co‐occurring species at finer scales. In North America, grassland and shrubland songbird populations are declining faster than other avian groups. Conservation of sage‐grouse habitats may protect songbird habitats where distributions overlap. To assess the umbrella species concept at fine scales, we quantified nest‐site selection for a sagebrush‐obligate songbird, the Brewer's sparrow ( Spizella breweri ). We then compared the fine‐scale habitat variables that influenced Brewer's sparrow nest‐site selection with fine‐scale nest‐site selection for sage‐grouse in the Powder River Basin region of northeastern Wyoming, USA. We modeled nest‐site selection using conditional logistic regression for Brewer's sparrow (2016–2017) and logistic regression for sage‐grouse (2004–2007). Both species selected nest sites with higher visual obstruction, shrub height, and branching density, although the selection for higher shrub height was stronger for sage‐grouse. Brewer's sparrows selected nest shrubs with higher percentage of living foliage (vigor), and the opposite was shown for sage‐grouse. At the nest site, based on the variables we measured, our results suggest that Brewer's sparrows and sage‐grouse select for similar habitat attributes, with the exception of shrub vigor of the nest shrub. The stronger selection for more vigorous shrubs in Brewer's sparrows may be because they nest in shrubs, rather than on the ground under shrubs (as in sage‐grouse). Most of the conservation objectives for protection of sage‐grouse habitats appear to be beneficial or inconsequential for Brewer's sparrow. Local habitat management for sage‐grouse as a proxy for conservation of other species may be justified if the microhabitat preferences of the species under the umbrella are understood to avoid unintentional negative effects. © 2019 The Wildlife Society.